Matthew Simpson papers - Simpson, Matthew, 1811-1884.
Family and general correspondence, diaries, journals, speeches, sermons, writings, notebooks, notes, printed matter, scrapbooks, and other papers relating to Simpson's presidency of Indiana Asbury University, Greencastle, Ind.; service as a Methodist Episcopal bishop; years as a circuit preacher; editorship of the Western Christian Advocate in Cincinnati, Ohio; travels in Europe; early life in Ohio and Pennsylvania; and family matters. Subjects include division in the church over the slavery question, reorganization of the Methodist Church in the South after the Civil War, Methodist Church expansion during the 19th century, and the church and science. Correspondents include Edward Raymond Ames, Montgomery Blair, James Harlan, Edmund S. Janes, and Thomas A. Morris.
Methodist clergyman, educator, editor, and orator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ames, Edward Raymond, -- 1806-1879 -- Correspondence; Blair, Montgomery, -- 1813-1883 -- Correspondence; Harlan, James, -- 1820-1899 -- Correspondence; Janes, Edmund S. -- 1807-1876 -- Correspondence; Morris, Thomas A. -- 1794-1874 -- Correspondence; Simpson family; Simpson family -- Correspondence; Indiana Asbury University (Greencastle, Ind.); Methodist Episcopal Church -- Bishops; Methodist Episcopal Church -- History -- 19th century; Methodist Episcopal Church -- Periodicals; Methodist Episcopal Church -- Southern States; Western Christian advocate; Circuit riders; Religion and science; Slavery -- United States; Slavery and the church -- United States; Universities and colleges -- Indiana -- Greencastle; Cincinnati (Ohio) -- History; Europe -- Description and travel; Ohio -- Social life and customs; Pennsylvania -- Social life and customs; Clergy; Editors; Educators; Orators